The falcon's eyes : a novel - Stanfill, Francesca (Harper, an imprint of HarperCollinsPublishers, 2022)
"Illuminating the end of the twelfth century and the notorious queen--Eleanor of Aquitaine--who dominated it, this sweeping, suspenseful tale follows Isabelle, a spirited, questing young woman, who defies convention--and her controlling, falconry-obsessed husband--to lead an extraordinary life"--